Not just Trigonometry

Geometry Level 4

csc 2 π 7 + csc 2 2 π 7 + csc 2 3 π 7 = ? \large \csc^2\dfrac{\pi}{7} + \csc^2\dfrac{2\pi}{7} + \csc^2\dfrac{3\pi}{7} = \, ?


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Vatsalya Tandon
Apr 17, 2016

We know that...

csc 2 x = 1 + cot 2 x \csc^2 x = 1 + \cot^2 x

Thus, the given expression becomes:

3 + cot 2 π 7 + cot 2 2 π 7 + cot 2 3 π 7 3 + \cot^2\frac{\pi}{7} + \cot^2\frac{2\pi}{7} + \cot^2\frac{3\pi}{7}

Or, 3 + r = 1 n cot 2 r π 2 n + 1 3 + \sum_{r=1}^{n}\cot ^2 \frac{r\pi}{2n+1}

Here n = 3 n=3

Now let us assume, sin ( 2 n + 1 ) x = 0 \sin (2n+1)x = 0

( 2 n + 1 ) x = m π \therefore (2n+1)x = m\pi

x = m π ( 2 n + 1 ) \therefore x = \frac{m\pi}{(2n+1)}

Also, let us have z = cos x + i sin x z= \cos x + i\sin x

z ( 2 n + 1 ) = cos ( 2 n + 1 ) x + i sin ( 2 n + 1 ) x ( 1 ) \therefore {z}^{(2n+1)} = \cos(2n+1)x + i\sin(2n+1)x \cdots \left (1 \right )

By, using binomial expansion, we get:-

z ( 2 n + 1 ) = C 0 cos ( 2 n + 1 ) x + C 1 ( cos 2 n x ) . i . ( sin x ) C 2 ( cos 2 n 1 x ) ( sin 2 x ) C 3 ( cos 2 ( n 1 ) x ) . i . ( sin 3 x ) ( 2 ) z^{(2n+1)} = C_0 \cos^{(2n+1)} x + C_1 (\cos^{2{n}}x).i.(\sin x) - C_2 (\cos^{2{n-1}}x)(\sin^2 x) - C_3 (\cos^{2{(n-1)}}x).i.(\sin^3 x) \cdots \left ( 2 \right )

Equating imaginary parts of 1 and 2, we get,

sin ( 2 n + 1 ) x = C 1 ( cos 2 n x ) ( sin x ) C 3 ( cos 2 ( n 1 ) x ) ( sin 3 x ) \sin(2n+1)x = C_1 (\cos^{2{n}}x)(\sin x) - C_3 (\cos^{2{(n-1)}}x)(\sin^3 x) \cdots

Multiplying and Dividing each term of RHS to get cot 2 x \cot^2 x , also let us assume c o t 2 x = y cot^2 x = y

sin ( 2 n + 1 ) x = C 1 ( y n ) ( sin ( 2 n + 1 ) x ) C 3 ( y n 1 ) ( sin 2 n + 1 x ) \sin(2n+1)x = C_1 (y^n)(\sin^{(2n+1)} x) - C_3 (y^{n-1})(\sin^{2n+1} x) \cdots

sin ( 2 n + 1 ) x = ( sin 2 n + 1 x ) [ C 1 ( y n ) C 3 ( y n 1 ) ] \sin(2n+1)x = ( \sin^{2n+1}x) [C_1 (y^n) - C_3 (y^{n-1}) \cdots]

Now we must see that in RHS s i n 2 n + 1 x 0 sin^{2n+1}x \neq 0

Therefore, the second expression is zero and for finding the above sigma, we see that we need the sum of roots of the second expression amounts to the sigma operation.

Thus, sum of roots:

b a = 2 n + 1 C 3 2 n + 1 C 1 \frac{-b}{a} = \frac{^{2n+1}\textrm{C}_{3}}{^{2n+1}\textrm{C}_{1}}

b a = ( 2 n ) ( 2 n 1 ) 6 \frac{-b}{a} = \frac{(2n)(2n-1)}{6}

Plugging in n = 3 n=3 , we get:

r = 1 n cot 2 r π 2 n + 1 = 5 \sum_{r=1}^{n}\cot ^2 \frac{r\pi}{2n+1} = 5

Therefore the value of the expression is equal to 3 + 5 = 8 3 +5 = 8

Latex Tip: \text{Latex Tip:} Use \dbinom command for combinations.For example ( 3 2 ) \dbinom{3}{2}

Harry Jones - 4 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...